Polymer membranes for biofouling mitigation: a review. Issue 17 (22nd November 2019) - Naz, Asima; Sattar, Rabia; Siddiq, Muhammad
ABSTRACT: Nanofiltration (NF) membranes were introduced during the '80s with characteristics in between those of reverse osmosis and ultrafiltration membranes. This article aims at critically reviewing advances in NF research including relevance of fabrication techniques, modifications, and current problems. We also have a comprehensive look at fouling mitigation as well as its prevention by treating NF membranes with functionalized carbon nanotubes. It was found that some parameters such as porosity, crystallinity of polymer and hydrophobicity/hydrophilicity can affect the performance of membranes. NF membranes can be widely utilized in broad spectrum of applications particularly in desalination and wastewater treatment. Abbreviations: VA: Vertically align; MMM: Mixed matrix membrane; PAN: Polyacrylonitril; PAA: Poly(amic acid); HA: Humic Acid; BPA: Bisphenol A; MPD: m-phenylene diamine; PES: Polyether sulfone; LBL: Layer by layer; PEO: Poly(ethylene-oxide); PVA: Poly(vinyl alcohol); TR: Thermally rearranged; TR-PBO: Thermally rearranged polybenzoxazole; CVD: Chemical vapor deposition; PMMA: Poly(methy methacrylate; PET: polyetherimid; Psf: polysulfone; FSCMs: Fixed site carrier membranes; SILMs: Supported ionic liquid membranes; TFC: Thin film composite; IP: Interfacial polymerization; PE: Polyethylene; PP: Polypropylene; PC: Polycarbonate; PET: Polyethylene naphthalate; AMPS: 2-acrylamido-2-methylpropanesulfonic acid; NPs: Nanoparticles; TFC: Thin film composite; MPD: m-phenylenediamine; TMC: Trimesoyl chloride; CPES: Carboxylic polyethersulfon; ECPN: Electrically conducting polymer nanocomposites; mPDA:1, 3-phenylenediamine; SWCNTs: Single wall carbon nanotubes; MWCNT: Multi wall carbon nanotubes; PVC: Polyvinyl chloride; NOMs: Natural organic matter; AAO: Anodic aluminium oxide; PVDF: Polyvinylidene fluoride; MD: Membrane distillation; PHGH: Polyhexamethylene guanidine hydrochloride; TMBPA: Tetramethyl Bisphenol A; APDEMS: Aminopropyldiethoxymethylsilane; PLGA: Poly(lactide-co-glycolide); PEVA: Poly(ethylene-co-vinyl alcohol); PCL: Poly(ε-caprolactone); PS: Polystyrene; PU: Polyurethane; PGA: Poly(glycolide); TE: Tissue engineering; SEM: Scanning electron microscopy; TEM: Transmission electron microscopy; EDX: Energy dispersive X-ray spectroscopy; BOD: Biological oxygen demand; COD: Chemical oxygen demand; TSS: Total suspended solids; SMBR: Submerged membrane bioreactor; NVP: N-vinyl-2-pyrrolidinone; NVF: N-vinylformamide; NVC: N-vinylcaprolactam; HEMA: 2-hydroxylethyl methacrylate; AA: Acrylic acid; AAm: Acrylamide; AAG: 2-Acrylamidoglycolic acid; AMPS: 2-acrylamido-methyl-propane sulfonic acid; SPMA: 3-sulfopropyl methacrylate; GAMA: d-gluconamidoethyl methacrylate; MPDSAH inner salt: [(methacryloylamino)propyl]-dimethyl (3-sulfopropyl) ammonium hydroxide inner salt; BSA: Bovine serum albumin; PDA: 2, 4-phenylenediamine; EDA: Ethylene diamine; PDMSO: Poly(dimethylsiloxane); GPUs: Gas Permeation Units; ZIF: Zeolitic imidazolate framework; UF: ultrafiltration; MF: microfiltration; RO: Reverse osmosis; MD: Membrane distillation GRAPHICAL ABSTRACT: